Detection of cell-free foetal DNA fraction in female-foetus bearing pregnancies using X-chromosomal insertion/deletion polymorphisms examined by digital droplet PCR - Zednikova, Iveta; Pazourkova, Eva; Lassakova, Sona; Vesela, Barbora; Korabecna, Marie (Scientific reports, 2020)
In families with X-linked recessive diseases, foetal sex is determined prenatally by detection of Y-chromosomal sequences in cell-free foetal DNA (cffDNA) in maternal plasma. The same procedure is used to confirm the cffDNA presence during non-invasive prenatal RhD incompatibility testing but there are no generally accepted markers for the detection of cffDNA fraction in female-foetus bearing pregnancies. We present a methodology allowing the detection of paternal X-chromosomal alleles on maternal background and the confirmation of female sex of the foetus by positive amplification signals. Using digital droplet PCR (ddPCR) we examined X-chromosomal INDEL (insertion/deletion) polymorphisms: rs2307932, rs16397, rs16637, rs3048996, rs16680 in buccal swabs of 50 females to obtain the population data. For all INDELs, we determined the limits of detection for each ddPCR assay. We examined the cffDNA from 63 pregnant women bearing Y-chromosome negative foetuses. The analysis with this set of INDELs led to informative results in 66.67% of examined female-foetus bearing pregnancies. Although the population data predicted higher informativity (74%) we provided the proof of principle of this methodology. We successfully applied this methodology in prenatal diagnostics in a family with Wiscott-Aldrich syndrome and in pregnancies tested for the risk of RhD incompatibility.
Keywords: dospělí; Genetic Testing; Cell-Free Nucleic Acids; plod; Female; polymerázová řetězová reakce; Adult; Polymerase Chain Reaction; ženské pohlaví; prenatální diagnóza; lidé; Fetus; mutace INDEL; těhotenství; Prenatal Diagnosis; volné cirkulující nukleové kyseliny; INDEL Mutation; lidské chromozomy X; analýza určování pohlaví; Chromosomes, Human, X; polymorfismus genetický; genetické testování; Pregnancy; Polymorphism, Genetic; Sex Determination Analysis; Humans